Development of lower leg strength and flexibility with the strength shoe - Cook, S. D.; Schultz, G.; Omey, M. L.; Wolf, M. W.; Brunet, M. F. (The American Journal of Sports Medicine, 1993)
Two groups of six male track athletes were exposed to an eight-week training program either wearing a strength shoe (4-inch sole platform) or a normal shoe. Specific workouts were for 45 min three times per week. The shoe produced no benefit in ankle joint dorsi-flexion, vertical leap, 40-yd dash, or calf circumference. The shoe produced shin splints. Implication: Wearing a strength shoe did not improve performance or function in the lower leg. It was associated with the excessive use injury of shin splints.